Physiologically‐based pharmacokinetic modeling of oxcarbazepine and levetiracetam during adjunctive antiepileptic therapy in children and adolescents - Jaydeep Sinha; Eleni Karatza; Daniel Gonzalez (Wiley, 2022)
Abstract Oxcarbazepine (OXZ) and levetiracetam (LEV) are two new generation anti‐epileptic drugs, often co‐administered in children with enzyme‐inducing antiepileptic drugs (EIAEDs). The anti‐epileptic effect of OXZ and LEV are linked to the exposure of OXZ's active metabolite 10‐monohydroxy derivative (MHD) and (the parent) LEV, respectively. However, little is known about the confounding effect of age and EIAEDs on the pharmacokinetics (PKs) of MHD and LEV. To address this knowledge gap, physiologically‐based pharmacokinetic (PBPK) modeling was performed in the PK‐Sim software using literature data from children greater than or equal to 2 years of age. Age‐related changes in clearance (CL) of MHD and LEV were characterized, both in the presence (group 1) and absence (group 2) of concomitant EIAEDs. The drug‐drug interaction effect of EIAEDs was estimated as the difference in CL estimates between groups 1 and 2. PBPK modeling suggests that bodyweight normalized CL (ml/min/kg) is higher in younger children than their older counterparts (i.e., due to an influence of age). Concomitant EIAEDs further increase MHD's CL to a fixed extent of 25% at any age, but EIAEDs' effect on LEV's CL increases with age from 20% (at 2 years) to 30% (at adolescence). Simulations with the maximum recommended doses (MRDs) revealed that children between 2 and 4 years and greater than 4 years, who are not on EIAEDs, are at risk of exceeding the reference exposure range for OXZ and LEV, respectively. This analysis demonstrates the use of PBPK modeling in understanding the confounding effect of age and comedications on PKs in children and adolescents.